Formulasi Nanoenkapsulasi Ekstrak Kacang Gude (Cajanus cajan L. (Huth.)) sebagai Antidiabetes - Rifkarosita Putri Ginaris; Anggi Aryadi; Nadya Afifa; Arief Kusuma Wardani; Lyna L. Indrayati; Blegoh Iwan Santoso (LPPM-KI - POLTEKKES PIM (Formerly AKAFARMA-AKFAR PIM, 2026)
Pigeon pea (Cajanus cajan L. (Huth.)) contains flavonoids that exhibit potential antidiabetic activity through the inhibition of the α-glucosidase enzyme. The main limitation in the application of flavonoid compounds is their low solubility and stability. Nanoencapsulation using chitosan–TPP via a simple ionic gelation method can enhance the stability and bioactivity of active compounds. This study aimed to develop a nanoencapsulation formulation of pigeon pea extract and to evaluate its physical characteristics, stability, and α-glucosidase inhibitory activity. The research was conducted using variations in nanoencapsulation extract concentrations: F1 (0.2%), F2 (0.4%), and F3 (1%). Physical characterization included particle size, polydispersity index (PDI), and zeta potential, along with a freeze–thaw stability test for five cycles. Antidiabetic activity was assessed by measuring α-glucosidase inhibition and determining the IC₅₀ value. Data were analyzed using one-way ANOVA followed by Tukey’s post hoc test (p < 0.05). The results showed that particle size decreased from 290.40 nm (F1) to 198.30 nm (F3), with polydispersity index values below 0.3 for F2 and F3. The zeta potential ranged from −28.10 to −36.10 mV. F3 demonstrated the highest stability and the strongest antidiabetic activity with an IC₅₀ value of 68 ppm (p < 0.05). In conclusion, the nanoencapsulation formulation of pigeon pea extract produced small-sized, stable particles with effective α-glucosidase inhibitory activity. The optimal formulation was F3, which shows potential for further development as a natural-based antidiabetic nanoencapsulation system.